Electrophoresis of pH‐regulated particles in the presence of multiple ionic species. Issue 2 (8th November 2013) - Hsu, Chien; Lee, Duu‐Jong; Hsu, Jyh‐Ping; Wang, Nan; Tseng, Shiojenn
<x xml:space="preserve">Abstract</x> An electrophoresis model taking account of the pH‐regulated nature of particles and the presence of multiple ionic species is proposed for arbitrary surface potential and double‐layer thickness. It successfully simulated the electrophoretic behavior of Fe3O4 nanoparticles in an aqueous NaCl solution with pH adjusted by HCl and NaOH. The estimated zeta potential is compared with those from the conventional models, Smoluchowski's, Hückel's, and Henry's formulas. Due to the violation of the assumption of low and constant surface potential, these formulas yielded appreciable deviations (e.g., 23–30 mV at pH 9). With the surface charge density measured by titration and the zeta potential by electrophoresis, the true surface potential is estimated through a triple‐layer model. The estimated true potential is typically 1.5–10 times larger than the zeta potential, implying that using the latter in relevant calculations (e.g., stability and critical coagulation concentration) might yield appreciable deviation. © 2013 American Institute of Chemical Engineers AIChE J 60: 451–458, 2014